Developmental Irregularity and Abnormal Elytra Formation in the Oriental Wood Borer Induced by Physical Disturbance. Issue 1 (8th February 2018) - Bong, Lee-Jin; Neoh, Kok-Boon; Yoshimura, Tsuyoshi
Abstract: Teratological deformity in arthropods may arise spontaneously or be induced by chemicals, mutagens, diseases, and physical disturbance. Coleopterans are known to be sensitive to physical disturbance, but detailed studies of how physical disturbance affects the juvenile development and causes deformities are limited. In this study, larval oriental wood borers Heterobostrychus aequalis (Waterhouse) in three weight categories (2 to <10 mg, 10 to <26 mg, and 26 to 36 mg) were used to examine the development of immature beetles when exposed to daily physical disturbance (i.e., handling). Morphological changes induced in the immature and adult stages were observed for disturbed individuals. Handled larvae were highly susceptible to physical disturbance, as none of them survived to the end of the experiment, regardless of their initial weight group. Unhandled larvae molted twice before turning into pupae, whereas handled larvae took longer to develop and underwent irregular molting. Handled larvae also exhibited various levels of morphological abnormality in the pupal stage; in particular, the elytra were deformed, the abdomen and head capsule were broader than normal. It is speculated that the irregularity and deformity observed in the handled larvae might be due to hormone alteration resulting from physical disturbance. In addition, the extensively exposed abdominal parts of deformed beetles might have increased the risk of dehydration and disease attack, which would have resulted in premature mortality.